2016
DOI: 10.1111/ans.13606
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of the utility of routine neuromonitoring for an established thyroid surgical practice

Abstract: Routine IONM provides intraoperative information to a high-volume thyroid surgeon regarding the recurrent and external nerves over and above direct visualization alone, and its utility could not be predicted by operative indication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…In our primary surgery cases, an additional identification rate of 31.2% of nonvisualized branches by IONM revealed the significant contribution of nerve monitoring to EBSLN identification during upper pole dissection. Recent studies have reported an IONM contribution rate of up to 50% [13181920232425]. Therefore, on the basis of our results in primary thyroid surgery, functional identification rates of the EBSLN could exceed 95% due to appropriate anatomical dissection and proper use of electrophysiological monitoring.…”
Section: Discussionmentioning
confidence: 70%
“…In our primary surgery cases, an additional identification rate of 31.2% of nonvisualized branches by IONM revealed the significant contribution of nerve monitoring to EBSLN identification during upper pole dissection. Recent studies have reported an IONM contribution rate of up to 50% [13181920232425]. Therefore, on the basis of our results in primary thyroid surgery, functional identification rates of the EBSLN could exceed 95% due to appropriate anatomical dissection and proper use of electrophysiological monitoring.…”
Section: Discussionmentioning
confidence: 70%
“…Visual identification of the EBSLN was carried out as reported previously and confirmed using the nerve monitor. A positive result was recorded when strong and simultaneous contraction of the pars recta and pars oblique components of the cricothyroid muscle was observed.…”
Section: Methodsmentioning
confidence: 99%
“…Gurleyik et al found that IONM recognized 65.3% (in the first surgical procedure) and 30.4% (in subsequent surgical procedures) of the EBSLNs that were identified by visual inspection during surgery, and 55 of the 97 unrecognized nerves were identified by IONM (26). Lee et al (27) showed that IONM could improve the identification rate of the EBSLN in high-risk surgeries (Cernea type 2B) by 15.9%. Engelsman et al reported that the identification rate of the EBSLN using IONM was as high as 98.8% (28).…”
Section: Ionm Highlightsmentioning
confidence: 99%